The development and validation literacy scale for pre-service mathematics teachers - Ying Zhou; Xiaofeng Lan (Research and Social Study Institute, 2020)
The 21st century is an era in which education determines the future of society. The relevant theoretical research on core literacy is mainly carried out around students, and the research on the core literacy of pre-service mathematics teachers in ethnic areas has not yet begun. By consulting literature and existing mature questionnaires, combined with pre-service mathematics teachers' characteristics in ethnic areas, a